PALLIDOTOMY IN PARKINSONIAN DISEASE: THE RENAISSANCE - Aurangzeb Kalhoro; Abdul Basit Sattar; Abdul Sattar M. Hashim; Abid Saleem (Journal of University Medical & Dental College, 2021)
ABSTRACT: BACKGROUND & OBJECTIVE: To assess the results of pallidotomy in Parkinson’s disease, and its effect on improving the lifestyle of the patients and cost-effectiveness. METHODOLOGY: A descriptive study was conducted at Neuro-Spinal & Cancer Care Institute, Karachi from June 2014 to January 2020. Patients who were known case of Parkinson’s disease refractory to medication and developed side effects to medication were included in the study and patients with previous brain surgery, associated brain disorders like Alzheimer’s disease, basal ganglia lesion, brain trauma were excluded. All patients were treated by pallidotomy on the contralateral side. The significance of the difference between groups to compare between the pre-op or post-op treatments was calculated through non-parametric assessment Kruskal-Wallis tests. RESULTS: The mean age of the patients was around 57 years. There were 34(81%) male and 8(19%) female patients’ Maximum number of patients who were more than 45 years, were having a left-sided proportion. More male patients were having a left-sided proportion as compared to female patients. The majority of patients (57.5%) were having dyskinesia as q primary symptom. A significant difference (p-value <0.001) existed in pre & post-operative UPDRS-III scores. A significant difference (p-value <0.001) also existed between on & off medications UPDRS- III (pre-op/post-op) scores. CONCLUSION: The result of pallidotomy is promising especially for unilateral pallidotomy to minimize the risk of cognition and speech disorder and long-term follow-up is needed to prove the statement further. Currently, pallidotomy is associated with minimal complications, more effective, and improving the quality of life of Parkinsonian patients.